8.INTERLEUKIN-4 SINGLE NUCLEOTIDE POLYMORPHISM C-590T POLYMORPHISMS IN RELATION TO ASTHMA (Iraqi Journal of Medical Sciences, 2018)
Background: Single nucleotide polymorphisms in the promoter regions of genes encoding for some interleukins may associate with occurrence of asthma.Objective: To investigate the association of single nucleotide polymorphisms of interleukin-4 (IL-4) (C-590T) and asthma.Methods: Forty-five patients with asthma and 40 apparently healthy subjects (represent the control group) were enrolled in this study. Blood samples were collected from both patients and controls. DNA was extracted from blood samples and gene fragments corresponding to IL-4 C-590T were amplified with specific primers using conventional PCR technique. Results: The heterozygote genotypes of IL-4 C-590T (CT) showed significant association with asthma (OR = 3.922, 95% CI= 1.153-13.339, P = 0.028). Conclusion: These results suggest the significance of IL-4 C-590T polymorphism as a risk factor for asthma.Keywords: Asthma, interleukin-4, polymorphismCitation: Gaidan, Abbas AA, Hassan MA, Hashim HM. Interleukin-4 single nucleotide polymorphism C-590T polymorphisms in relation to asthma. Iraqi JMS. 2018; Vol. 16(1): 51-56. doi: 10.22578/IJMS.16.1.8
Keywords: Asthma; interleukin4; polymorphism